Ninety Day Post Discharge Outcome in Acute Exacerbation of Chronic Obstructive Pulmonary Disease Using the PEARL Score - Joshi, Aishana; Shrestha, Tirtha Man; Pant, Pankaj; Shakya, Yogendra Man (Journal of Nepal Health Research Council, 2021)
Background: Chronic obstructive pulmonary disease exacerbation is a leading cause of frequent hospitalizations imposing substantial global health burden. The 90 day post discharge period has been associated with higher readmission rates and substantial risk of death. The aim of this study was to assess post discharge 90 day outcome in patients admitted with acute Chronic obstructive pulmonary disease exacerbation using the PEARL score.Methods: A longitudinal study was conducted at Tribhuvan University Teaching hospital from February 2019 to November 2019. Patients admitted in respiratory ward with acute Chronic obstructive pulmonary disease exacerbation were stratified into low, intermediate and high risk groups using PEARL score and post discharge 90 day outcome was assessed. Data entry and analysis was done in SPSS version 20.0. Descriptive and inferential statistics were performed.Results: A total of 102 patients were included for final analysis. Mean age of patients was 70.54 ± 10.85 years. There were 53.9% male. Intermediate and high risk PEARL groups had the highest proportion of readmission within 90 days of discharge which was found to be 23 (52.3%) and 9 (50%) respectively. High risk PEARL group had the highest proportion of death within 90 days (11.1%). The difference in these outcomes among three PEARL groups was found to be statistically significant (p-value < 0.05).Conclusions: PEARL score is a simple tool that can be applied at bedside in assessing 90 dayrisk of readmission or death in acute Chronic obstructive pulmonary disease exacerbation. This can be beneficial in post-discharge planning and early referral especially in resource limited health care setting where advanced facilities are not available.Keywords: COPD; ninety day outcome; PEARL score